Funkcja superdźwigni operacyjnej - Mielcarek, Jarosław (The function of operating superleverage, 2006)
The function of operating superleverage turns out to be a linear demand rate growth function. With the help of the function one can determine the profit rate growth for changes in all factors, i.e. prices, demand, variable costs and fixed costs. Its slope coefficient is determined by the sum of the demand operating leverage and profit growth rates for changes in the level of prices and variable costs. The absolute term equals the profit rate growth for the changes of all additive factors. All parameters specified in the slope coefficient and the absolute term are determined by initial conditions. Presented demand growth rates formulas for the characteristic points of the function, such as break-even point or constant profit point, enable us to explain the changes taking place in profit and the final demand operating leverage under the influence of the changes in all factors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 268-277